Faktor Yang Mempengaruhi Peningkatan Penggunaan QRIS Sebagai Alat Pembayaran Di Kalangan Mahasiswa Perguruan Tinggi Swasta Kota Mataram - Rizki Fitriani; Armiani; Sigit Ary Wijayanto (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to examine the factors influencing the increase in the use of QRIS among private university students in the city of Mataram. This research variable consists of 4 (four) independent variables, namely financial literacy (X1), Perception of risk (X2), Perception of Convenience (X3), and Perception of Benefit (X4) and the dependent variable is Increased Use (Y). This research uses associative quantitative methods. The population of this research is Mataram City Private University Students. Samples were taken using purposive sampling. Data was obtained by distributing 100 questionnaires to respondents. Data were analyzed using Multiple Linear Regression. The results of this research show that the variables of financial literacy and risk perception do not have a significant effect on increasing the use of QRIS. On the other hand, the variables of perceived convenience and perceived usefulness have a positive and significant effect on increasing the use of QRIS. The results of this research also show that the independent variables (financial literacy, perceived risk, perceived convenience, and perceived benefits) are able to explain the dependent variable (increased use) of 22.6%. Meanwhile, the remaining 77.4% is influenced by other variables outside the multiple linear regression model